MULTI-OBJECTIVE OPTIMIZATION MODEL FOR BIOENERGY SUPPLY CHAIN DISTRIBUTION - Krisnaningsih, Erni; Dwiyatno, Saleh; Cahyadi, Dadi; Rasjidin, Roesfiansjah (Department of Agroindustrial Technology, Bogor Agricultural University, 2025)
Determining optimal distribution routes in managing efficient transportation distances is a challenge in the bioenergy supply chain. Adequate distribution arrangements can improve distribution in the bioenergy supply chain. Optimizing distribution arrangements can help reduce transportation costs, avoid delays, and improve distribution efficiency. The optimal distribution strategy must consider choosing routes that minimize distribution distances from agricultural centres to power plants. This study aimed to determine the location of collection points and optimal distribution routes in the distribution of the bioenergy supply chain. Centre of gravity (COG) method for locating collection centres. Determination of optimal distribution routes with a combination of ME-MCDM and spatial Dijkstra approaches. The results showed that the centre point at -60.53'42.6